BOUNDED TREE-DEPTH, PATH-DISTANCE-WIDTH, AND LINEAR-WIDTH OF GRAPHS - Fujita, Takaaki (Diponegoro University, 2024)
The study of width parameters and related graph parameters is an activearea of research in graph theory. In this brief paper, we explore the upper and lowerbounds of graph parameters, including path-distance-width, tree-distance-width, tree-depth, and linear-width. These bounds are crucial for understanding the complexityand structure of graphs.